2003
DOI: 10.1097/01.ju.0000049228.37887.4d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Poly (Adenosine Diphosphate-Ribose) Polymerase Inhibitors on Biochemical Changes in Testicular Ischemia-Reperfusion Injury

Abstract: These data emphasize that poly (ADP-ribose) polymerase may have a role in testicular damage caused by ischemia-reperfusion and the inhibition of poly (ADP-ribose) polymerase may be a novel approach to therapy for ischemia-reperfusion injury of the testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
3
28
2
Order By: Relevance
“…14 Bozlu et al showed that IR injury elevated NO production in a model of testicular torsion and detorsion in rat. 15 Also, results in previous studies suggest that NO has an important role in damaging the testis via IR injury. 40 Similarly our study showed that IR injury due to testicular torsion and detorsion elevated NO production in a rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Bozlu et al showed that IR injury elevated NO production in a model of testicular torsion and detorsion in rat. 15 Also, results in previous studies suggest that NO has an important role in damaging the testis via IR injury. 40 Similarly our study showed that IR injury due to testicular torsion and detorsion elevated NO production in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…6 Lots of chemicals, drugs and physical methods such as intratesticular testosterone, biocompatible surfactant (tetronic 1107), allopurinol, vitamin E, NG-nitro-Larginine methyl ester (a precursor of NO), polyethylene glycol-superoxide dismutase, immunosuppression with cyclosporinee and prednisone, caffeic acid phenethyl ester, poly (ADP-ribose) polymerase inhibitors, pentoxifylline, vasoactive intestinal polypeptide, zinc aspartate, melatonin, hyperbaric oxygen therapy and chemical sympathectomy have been used to prevent IR injury in testicular torsion and detorsion. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] These products were found to be effective in preventing testicular damage. Trapidil has not been used in testicular IR injury previously.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that neutrophils recruited to the testis after torsion are potent generators of ROS. Several studies indicate that neutrophils are recruited to the testis as early as 4 h after I/R [26,28] . In the present study, MPO showed an increase in testicular tissue 4 h after I/R, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The testicular damage due to torsion and detorsion (T/D) shares resemblance with the phenomenon of ischemia-reperfusion (I/R) injury observed in other tissues [3]. A possible cause of the testicular injury due to torsion and detorsion is an I/R injury attributed to neutrophil infiltration and oxygen free radicals [4]. Several enzymes and drugs, such as melatonine, vitamins E and C, surfactane, and hyperbaric oxygen therapy, have been studied to prevent such injury in testis [5].…”
Section: Introductionmentioning
confidence: 97%